The power of trust: How does parents' failure mindset affect children's intelligence mindset?. (May 2023) - Liu, Guofang; Su, Qian; Han, Yulei
Abstract: Children's intelligence mindset plays an important role in their happiness and academic development. Several researchers have revealed the influence of parents' failure mindset on their children's intelligence mindset. This study examined this influence in Chinese culture and proposed that parents' academic trust is a mediator in the relationship between parents' failure mindset and children's intelligence mindset. In Study 1, 311 children (grades from 5 to 7; 171 were girls) and one of their parents provided their corresponding evaluations. Bootstrap analysis results demonstrated the effect of parents' failure mindset on children's intelligence mindset and the mediating role of parents' academic trust. In Study 2, 298 children (grades 5 and 6; 151 were girls) reported on their intelligence mindset and perceptions of their parents' failure mindset and academic trust. These results validated those of Study 1 and revealed that children's perceptions of their parents' beliefs exhibited the same effects as parents' self-evaluated beliefs. Therefore, we have found that parents with a failure-is-enhancing view are more likely to trust their children's academic potential and that these children thus develop a growth intelligence mindset. Highlights: Chinese parents' failure mindset influenced their children's intelligence mindset. Parents' failure-is-enhancing belief improved children's growth mindset. Parents' failure-is-enhancing belief increased their academic trust in the children. Parents' academic trust mediated the effect of failure mindset on growth mindset.